Competing risk analysis of cardiovascular disease risk in breast cancer patients receiving a radiation boost - Yvonne Koop; Femke Atsma; Marilot C.T. Batenburg; Hanneke Meijer; Femke van der Leij; Roxanne Gal; Sanne G.M. van Velzen; Ivana Išgum; Hester Vermeulen; Angela H.E.M. Maas; Saloua El Messaoudi; Helena M. Verkooijen (Cardio-Oncology, 2024)
Abstract Background Thoracic radiotherapy may damage the myocardium and arteries, increasing cardiovascular disease (CVD) risk. Women with a high local breast cancer (BC) recurrence risk may receive an additional radiation boost to the tumor bed. Objective We aimed to evaluate the CVD risk and specifically ischemic heart disease (IHD) in BC patients treated with a radiation boost, and investigated whether this was modified by age. Methods We identified 5260 BC patients receiving radiotherapy between 2005 and 2016 without a history of CVD. Boost data were derived from hospital records and the national cancer registry. Follow-up data on CVD events were obtained from Statistics Netherlands until December 31, 2018. The relation between CVD and boost was evaluated with competing risk survival analysis. Results 1917 (36.4%) received a boost. Mean follow-up was 80.3 months (SD37.1) and the mean age 57.8 years (SD10.7). Interaction between boost and age was observed for IHD: a boost was significantly associated with IHD incidence in patients younger than 40 years but not in patients over 40 years. The subdistribution hazard ratio (sHR) was calculated for ages from 25 to 75 years, showing a sHR range from 5.1 (95%CI 1.2–22.6) for 25-year old patients to sHR 0.5 (95%CI 0.2–1.02) for 75-year old patients. Conclusion In patients younger than 40, a radiation boost is significantly associated with an increased risk of CVD. In absolute terms, the increased risk was low. In older patients, there was no association between boost and CVD risk, which is likely a reflection of appropriate patient selection.